Effects of unsaturated fatty acid-rich diets supplemented with antioxidants on lipid and fatty acid metabolism in high-fat rats - Manyu Helian; Xian Niu; Xiaoqi Zhou; Qian Zou; Zeyuan Deng; Rong Liu; Liufeng Zheng; Jing Li (Food Science of Animal Products)
Diet, as the core means of obtaining nutrients in the human body, plays a key role in maintaining a state of health and influencing the development of diseases. High fat diets (HFD) can cause hyperlipidaemia, obesity, type 2 diabetes, hypertension, cardiovascular disease, and other diseases. Dietary interventions have emerged as effective adjunctive therapies, especially dietary fatty acids and antioxidant intake can improve dyslipidaemia induced by HFD. Here, to explore the effects of unsaturated fatty acid-rich diets supplemented with antioxidants on lipid and fatty acid metabolism in high-fat rats, 40 Sprague-Dawley rats (half male and half female) were divided into 4 groups and fed with basal diet (C), basal diet supplemented with 12.7% mixed oil (MO), mixed oil plus VE (50 mg/kg) (MOV), and mixed oil plus VE (50 mg/kg) and propolis (30 mg/kg) (MOVP) for 6 weeks. The unsaturated fatty acid-enriched mixed oil was added to meet the requirements of dietary fatty acid ratio: 27% saturated fatty acid (SFA), 32.5% monounsaturated fatty acid (MUFA), and 40.5% polyunsaturated fatty acid (PUFA) (n-6 PUFA/n-3 PUFA = 1:1). Blood lipid biochemical index as well as the profile of a total of fatty acids were determined in heart, liver, brain, muscle, subcutaneous fat, and kidney. HFD increased the level of total cholesterol (TC), triglyceride (TG) and low-density lipoprotein-cholesterol (LDL-C) and decreased the lever of high-density lipoprotein-cholesterol (HDL-C) in rat plasma and tissues. MO group increased contents of most unsaturated fatty acids, especially n-3 PUFAs, in all these organs, and a synergistic elevation in these unsaturated fatty acids was further observed in combination with VE and propolis. Hence, the addition of antioxidants could protect unsaturated fatty acids against oxidation, thereby reducing the onset and progression of diseases associated with an HFD.